A posttranslational modification of fimbriae drives pathogenicity in Klebsiella pneumoniae - Genevieve S. Dobihal; Kristen Lewis; Tian Huai Shen; Carmen M. Herrera; Lisa Yu; Jonathan Barasch; M. Stephen Trent; Josué Flores-Kim; Anne-Catrin Uhlemann (Proceedings of the National Academy of Sciences, 2026)
Antimicrobial resistance is a severe public health burden. Especially concerning are multidrug resistant (MDR) infections, which restrict treatment options and significantly increase mortality risk. A major cause of MDR infections worldwide is carbapenem-resistant Klebsiella pneumoniae (CR Kp ). The predominant CR Kp sequence type worldwide is ST258. However, the factors underlying ST258’s epidemic success are not well defined. Genomic analyses of clinical isolates of CR Kp have found that the two-component regulatory system CrrAB is a genomic feature of ST258, suggesting that it may contribute to its global dominance. Despite this, the molecular details underpinning CrrAB’s contribution to ST258 Kp biology and pathogenicity are poorly understood. We used RNA-sequencing to identify the regulon of CrrA and found that CrrAB induces the expression of a gene, encoding Crr-regulated fimbriae modifying protein (CfmP), that is essential for pathogenesis driven by this two-component system. We performed mass spectrometry analyses of fimbriae purified from Kp expressing or lacking cfmP and found that CfmP induces a novel oxidation to a histidine residue in the major pilin subunit of fimbriae, FimA. We demonstrate that this oxidation significantly increases host cell adhesion and high bacterial loads within the host. CrrAB also drives high antibiotic resistance in CR Kp . Thus, our results place CrrAB at the intersection of pathogenicity and antibiotic resistance supporting its function as an important regulatory system driving the global dominance of ST258.